TEKNOLOGI PENANGKAPAN IKAN PADA MASYARAKAT NELAYAN DI NAGARI PASAR LAMA AIR HAJI, KECAMATAN LINGGOSARI BAGANTI, KABUPATEN PESISIR SELATAN - Ermayanti Ermayanti (Universitas Andalas, 2015)
In the fishing community, fisheries economic sector will not be released to the role of traditional fisheries technology in various forms, such as ship or boat, fishing net (Wareng). Conditions of fishing tools that is still largely traditional and the number of workers is still high fisherman showing the condition of Pasar Lama Muaro Air Haji villages classified as areas considered to have pockets of poverty . This makes the fishing could not be further moves towards its efforts to develop the technology of fishing